Early Prediction of Hypoxic-Ischemic Brain Injury by a New Panel of Biomarkers in a Population of Term Newborns. (28th June 2018) - Negro, Simona; Benders, Manon J. N. L.; Tataranno, Maria Luisa; Coviello, Caterina; de Vries, Linda S.; van Bel, Frank; Groenendaal, Floris; Longini, Mariangela; Proietti, Fabrizio; Belvisi, Elisa; Buonocore, Giuseppe; Perrone, Serafina
Abstract : This research paper is aimed at evaluating the predictive role of a default panel of oxidative stress (OS) biomarkers for the early identification of infants at high risk of HIE and their validation through the correlation with MRI findings. A multicenter prospective observational study was performed between March 2012 and April 2015 in two European tertiary NICUs. Eighty-four term infants at risk for HIE (pH < 7, BE < −13 mmol/L, and 5 ′ Apgar < 5) were enrolled. Three were excluded for chromosomal abnormalities and one due to lack of blood samples. The final population was divided according to the severity of perinatal hypoxia into 2 groups: mild/moderate HIE and severe HIE. Advanced oxidation protein products (AOPP), non-protein-bound iron (NPBI), and F2-isoprostanes (F2-IsoPs) were measured in blood samples at P1 (4–6 hours), P2 (24–72 hours), and P3 (5 days), in both groups. MRIs were scored for the severity of brain injury, using a modified Barkovich score. The mean GA was 39.8 weeks (SD 1.4) and the mean birth weight 3538 grams (SD 660); 37 were females and 43 males. Significantly lower 5 ′ Apgar score, pH, and BE and higher Thompson score were found in group II compared to group I at birth. Group II showed significantly higher AOPP and NPBI levels than group I (mean (SD) AOPP: 15.7 (15.5) versus 34.1 (39.2), p = 0.033 ; NPBI 1.1 (2.5) versus 3.9 (4.4), p = 0.013 ) soon after birth (P1). No differences were observed in OS biomarker levels between the two groups at P2 and P3. A regression model, including adjustment for hypothermia treatment, gender, and time after birth, showed that AOPP levels and male gender were both risk factors for higher brain damage scores (AOPP: OR 3.6, 95% CI (1.1–12.2) and gender: OR 5.6, 95% CI (1.2–25.7), resp.). Newborns with severe asphyxia showed higher OS than those with mild asphyxia at birth. AOPP are significantly associated with the severity of brain injury assessed by MRI, especially in males.